(untitled) (Damascus University Journal of agriculture sciences, 2025)
This research was conducted at the Department of Food Sciences, Faculty of Agriculture, University of Damascus, with the aim of evaluating the chemical, processing and sensory properties of pan bread and biscuits produced from a flour mixture of a number of cereal grains (rice and maize) and pseudo-grains (quinoa and chia), to find a mixture of flour as an alternative to wheat flour in the production of special gluten-free foods. A mixture of 50% rice flour and 50% corn flour was adopted as control flour, then the control flour was replaced by 10% and 20% of quinoa flour and chia flour. The results of the approximate composition analysis of quinoa flour and chia flour showed a higher content of proteins, lipids, and fibers and a lower content of starch compared to rice flour and corn flour. Thus, replacing the control flour by 10% and 20% of quinoa flour and chia flour led to an increase in the content of moisture, ash, protein, lipids and fibers, and a decrease in starch content in both the pan bread and the resulting biscuits. Moreover, rice and corn bread loaf volume increased gradually, but it was also associated with an increase in its weight and a decrease in its specific volume, with an increase in the replacement levels of quinoa flour and chia flour, and a variation in the specific volume of all the studied combinations was observed. Furthermore, the addition of chia flour and quinoa flour in different proportions to the biscuit dough resulted in significant changes in the physical properties between the control biscuit and other gluten-free biscuit samples, and the highest value of spread ratio was recorded by the control biscuit sample and the lowest was recorded by the biscuit sample that contained 20% quinoa flour. It was also noted that the biscuit hardness increased when the control flour was replaced with quinoa flour and chia flour. On the other hand, the results of the sensory attributes evaluation indicated that the more quinoa flour and chia flour were added to the control flour, the better the loaf of bread became in terms of color, flavour, texture, taste and total acceptance, and the results of the sensory analysis of biscuits also indicated the possibility of producing biscuit samples from rice flour and corn flour, fortified with quinoa flour or chia flour, which were sensory acceptable.